ON STATE REGULATION OF TOURISM SPHERE - I. Kabirov (Russian Journal of Economics and Law)
The article views the historical bases of state regulation in tourism sphere, analyzes the changes in tourism legislation directly connected with the creation of financial guarantees institutions, and investigates the foreign experience of state policy in tourism sphere.